NILAI-NILAI KEPAHLAWANAN DALAM NOVEL AKU BUKAN JAMILAH KARYA ROBERT JUKI ARDI - Sari, Dewi Rantan; ., H. Martono; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstrak: Hasil penelitian yaitu: 1) nilai-nilai keberanian dilihat dari tokoh utama; (a) keberanian terhadap orangtua karena perjodohan, (b) keberanian teradap suami, (c) keberanian teradap keadaan. 2) nilai-nilai kesetiaan dilihat dari tokoh utama; (a) kesetiaan terhadap kedua orangtua, (b) kesetiaan terhadap suami, (c) kesetiaan terhadap sahabat. 3) nilai rela berkorban; (a) rela berkorban terhadap orangtua, (b) rela berkorban terhadap suami dan anak-anak, (c) rela berkorban terhadap perasaan. Kata kunci: Nilai kepahlawanan, Novel, Aku Bukan Jamilah Abstract: The results of the research are: 1) the values of the braveness refer to the main character; (a) the braveness toward parents because of marriage, (b) the braveness toward husband, (c) the braveness toward the condition. 2) The values of the loyalty refer to the main character; (a) the loyalty toward the parents, (b) the loyalty toward husband, (c) the loyalty toward friends. 3) The values of the willing of sacrifice; (a) the willing of sacrifice toward parents, (b) the willing of sacrifice toward husband and children, (c) the willing of sacrifice toward feeling. Keywords: The value of patriotism, Novel, Aku Bukan Jamilah